2014
DOI: 10.11114/jets.v2i2.290
|View full text |Cite
|
Sign up to set email alerts
|

Do Learners Fear More than Fear Itself: The Role of Fear in Law Students Educational Experiences

Abstract: While previous research has examined the various relationships between fear and learning in K-12 academic settings, the relationship is surprisingly unexplored amongst law students. Using a descriptive qualitative approach, we examine the role fear plays in law students" learning experiences. Through a series of semi-structured interviews a few areas of interest emerged including: fears related to disappointing family members and professors, as well as fears of peer judgment from classmates. The findings of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Martin et al found a reciprocal relationship between the psychological academic risk factors of anxiety, fear of failure, and lack of control over academic buoyancy [45]. Perrin et al have shown through qualitative research that the fear of disappointing others (relatives and peers) influences academic motivation [46]. In the context of performance-avoidance goals, the fear of failure increases anxiety that exerts negative influences on academic performance and motivation in pursuing goals, ultimately leading to withdrawal from the course [43,47].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Martin et al found a reciprocal relationship between the psychological academic risk factors of anxiety, fear of failure, and lack of control over academic buoyancy [45]. Perrin et al have shown through qualitative research that the fear of disappointing others (relatives and peers) influences academic motivation [46]. In the context of performance-avoidance goals, the fear of failure increases anxiety that exerts negative influences on academic performance and motivation in pursuing goals, ultimately leading to withdrawal from the course [43,47].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There are various reasons why students fear failure: parental expectations, the need to please authority figures (professors), fulfilling financial obligations, and so on (Perrin, O'Neil, Grimes, and Bryson, ). Fear can affect students both physically and cognitively and can manifest in missed or incomplete assignments or absences as a form of self‐sabotage.…”
Section: Teaching Survival Skillsmentioning
confidence: 99%
“…In educational environments, fear plays a pivotal role in shaping student behavior and attitudes. Perrin et al [11] highlighted that law students' fears, particularly about disappointing family and facing peer judgment, significantly affect their academic motivation. This finding underscores the emotional pressures students face and how these fears can drive their academic pursuits.…”
Section: Introductionmentioning
confidence: 99%